PENGARUH PANDEMI GLOBAL COVID-19 TERHADAP HUBUNGAN ANTARA STRUKTUR KEPEMILIKAN PERUSAHAAN DENGAN POTENSI TERJADINYA FINANCIAL DISTRESS - Destika Maulia; Anies Lastiati (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2023)
This research is to examine the effect of institutional ownership, foreign ownership and government ownership on financial distress. This study also examines whether the global covid-19 pandemic can change the effect of the relationship between institutional ownership, foreign ownership and government ownership on financial distress. This study uses a sample of infrastructure companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. The results show that institutional ownership, foreign ownership has a significant effect on financial distress which is proxied by the Altman Z-Score, while government ownership has no effect on financial distress. Meanwhile, the test results show that the effect of institutional ownership on the potential for financial distress weakened during the Covid pandemic. Meanwhile, the role of foreign owners is not different whether during a pandemic or not